The Struggle with Writing Anxiety: English Language Education Department Students and Thesis Proposal Completion - Syahrian Rasid; Hidayah Nor (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2024)
A thesis proposal is required of students before they can begin writing a thesis. Research background, theory, and technique are the only three chapters that make up the thesis proposal, as opposed to the thesis's five chapters. However, students can run into issues like anxiety when they are preparing a thesis proposal for several different reasons. Analysis of the anxiety felt by participants in the English Language Education Department is the goal of this study. This study sought to: (1) identify the different kinds of writing anxiety that students experienced when completing draft thesis proposals; (2) characterize the factors that contribute to writing anxiety in students; and (3) to learn about potential fixes that students came up with to finish the thesis proposal draft. Researchers employed the study design known as Narrative Inquiry by using narrative frameworks and interviews to gather data. The method of narrative analysis was applied to the collected data. The findings demonstrated that the participants had two different kinds of anxiety: somatic and cognitive anxiety. They reported experiencing a variety of anxiety-inducing factors, including insufficient writing experience or practice, a lack of subject-matter expertise, pressure to produce flawless work, time constraints, a high volume of assignments, inadequate writing methods, and poor self-confidence. To lessen their worry, the participants also tried a variety of strategies, including planning, unwinding, talking to others, and pausing.